ANALISIS NETWORK PLANNING MENGGUNAKAN CRITICAL PATH METHOD PADA PRODUKSI JOINT BRAKE ROD - Argadiraksa, Davina; Herwanto, Dene (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
The production process is very influential for the company, because it can provide profits from a production. If scheduling planning is not available, project activities will be delayed and less effective and project activities will be inefficient. Scheduling planning is optimal by applying the Critical Path Method (CPM). The advantage of the Critical Path Method (CPM) is that it can provide a list of project activities that are detrimental to the schedule, can set a schedule, identify important elements in a project, and find critical paths. This study aims to analyze component production scheduling and find critical paths of Joint Brake Rod component production activities by applying the Critical Path Method (CPM). This study obtained the results of the production time of Joint Brake Rod components by applying the Critical Path Method (CPM) is 37,953 seconds to produce products, where previously the company had time before applying the Critical Path Method (CPM) was 39,153 seconds. From the results of calculations before and after applying the method, this time decrease was 3.06%. In applying the Critical Path Method (CPM), an overview of the critical trajectory of network planning is obtained.